Geospatial Technology for Agricultural Land Site Suitability Assessment in Upper Vellar River Basin, South India - Ganesan, Prabakaran; Arumugam, Jothibasu (Anuário do Instituto de Geociências, 2025)
Agriculture is one of the oldest and prime activities of the human being. It has remained an important source of food. In spite of growing industrialization and urbanization in the world, nearly fifty per cent working population still engaged in agriculture. To make an in depth and comprehensive study, the main objectives present research is to analyze the changes in agricultural land use in the study region, to demarcate and to analyze the agricultural cropping land suitability and methods of cultivation, and to suggest remedial measures for the better agricultural planning and development of Upper Vellar River basin, Tamil Nadu, India using geospatial technology. Depending on their significance and importance in the agriculture seven different constraints and criteria were selected. The identification of different criteria depended on maximum limitation method that influences the product yield of agriculture which includes topographic wetness index (TWI), land use and land cover (LULC), soil, drainage density, slope, aspect and geology. The derived land suitability zones were classified into five classes i.e., not suitable, poor suitable, moderately suitable, highly suitable, and very high suitable zones. The not suitable zone cover 35 sq.km (1%) found in Belur, and Valapadi, poorly suitable zone covers 688 sq. km (8%) found in near Tammpampatti, Moderately suitable zone covers 976 sq.km (36%) found in northern part of study area, southern parts of the study area, highly suitable zone covers 1092 sq.km (43%) found in northern and central part of the study area and Very high suitable zone covers 152 sq.km (17%) found in Central and southern part of the total study area. Paddy crop is useful for developing in the highly suitable zone. The oilseed is the better decision to develop in the moderately suitable zone of the study area. In the low suitable region of study area, it is preferable to grow wheat. Examining the agricultural management plan of the study area shows that only 17% of the area is currently used for agricultural activities. Highly suitable lands for agriculture are the most suitable lands for agricultural production. These lands have the highest potential for agricultural production.